2016
DOI: 10.22159/ajpcr.2016.v9s3.14462
|View full text |Cite
|
Sign up to set email alerts
|

Acute Dermal Toxicity Study of Areca Catechu Linn. Extract in Sprague-Dawley Rats

Abstract: Objective: Areca catechu Linn. or biji pinang is one of the most widely used psychoactive substance with several hundred million users worldwide, predominantly in Southern Asia. However, details of the dermal toxicity of A. catechu L. are still undiscovered. The objective of this study is to investigate the in vivo acute dermal toxicity of aqueous extract of A. catechu L. at dose 15,000 mg/kg body weight in Sprague-Dawley rats. Methods:The acute dermal toxicity of A. catechu L. nut extract was investigated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 9 publications
3
12
0
3
Order By: Relevance
“…Our results from MWM test revealed that the extract at the doses of 1.5 and 3 mg/kg could reverse scopolamine-induced memory deficit in rats. Considering the fact that LD50 of the aqueous extract of betel nuts was found to be ≥15.000 mg/kg body weight (Sari et al, 2014;Kim et al, 2018), using very low toxic dose of extract would be beneficial to afford an herbal remedy possessing multi-target activity for the treatment of AD.…”
Section: Resultsmentioning
confidence: 99%
“…Our results from MWM test revealed that the extract at the doses of 1.5 and 3 mg/kg could reverse scopolamine-induced memory deficit in rats. Considering the fact that LD50 of the aqueous extract of betel nuts was found to be ≥15.000 mg/kg body weight (Sari et al, 2014;Kim et al, 2018), using very low toxic dose of extract would be beneficial to afford an herbal remedy possessing multi-target activity for the treatment of AD.…”
Section: Resultsmentioning
confidence: 99%
“…Acute oral toxicity is usually carried out in small groups of animal's gives information about the toxic profile of the plant extract. In any pharmaceutical preparation, acute oral toxicity studies are necessary to use in humans [14][15][16]. In the present study, the acute oral toxicity of ethanolic extract of A. grossus (L.f.) Goetgh.…”
Section: Discussionmentioning
confidence: 96%
“…Batang lurus, tidak bercabang dan kokoh mengakibatkan AC digunakan sebagai pembatas lahan maupun pembatas pekarangan (Silalahi 2014). Bagi masyarakat lokal Indonesia, AC juga digunakan sebagai tanaman pekarangan (Sari et al 2014) dan juga pembatas ladang (Silalahi et al 2014). Silalahi et al (2015b) menyatakan bahwa buah AC telah lama diperjual-belikan oleh pedagang tumbuhan obat di pasar Kabanjahe sebagai obat tradisonal, bahan ritual maupun tujuan lainnya.…”
Section: Pendahuluanunclassified
“…Bahan untuk menyirih pinang (AC), perbungaan atau daun Piper betle, dan kapur sirih mengakibatkan kanker oral di Asia Tenggara (Chiba et al 2001). Sari et al (2014) menyatakan bahwa di berbagai daerah Indonesia AC digunakan sebagai obat untuk mengatasi pendarahan seperti dalam menstruation, epistaxis ulcer, difteri, infeksi parasit, diare, dan disentri.…”
Section: Pendahuluanunclassified